Analisis Faktor-faktor yang Mempengaruhi Tingkat Kemiskinan di Sumatera Utara Menggunakan Structural Equation Modeling - Yessica Thania Silaban; Elly Rosmaini; Open Darnius; Asima Manurung (Konstanta : Jurnal Matematika dan Ilmu Pengetahuan Alam, 2024)
Poverty is a fundamental problem that is the center of attention of the government in any country. The aim of this research is to analyze the influence of education, unemployment, the Covid-19 pandemic and the human development index on poverty in North Sumatra. The data used in this research is secondary data based on time series available on the official website of the Central Statistics Agency in North Sumatra. This research data processing uses the help of SmartPLS 3 software. The research analysis used in this research is Structural Equation Modeling which shows that the variables education, unemployment, the Covid 19 pandemic and the human development index are exogenous variables and poverty is an endogenous variable. The research results obtained an R-Square value of 0.511 or 51.1%. The large value of the coefficient of determination shows that the independent variables consisting of education, unemployment, the Covid-19 pandemic and the human development index are able to explain the dependent variable, namely the poverty percentage of 51.1%. Meanwhile, the remaining 48.9% is explained by other variables not included in this research model. The human development index variable has a negative and significant effect on poverty of 0.678. For the Covid 19 Pandemic variable, it has a negative and significant effect on poverty of 0.267.